2010
DOI: 10.1073/pnas.1005776107
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin-3 mediates hydrogen peroxide uptake to regulate downstream intracellular signaling

Abstract: Hydrogen peroxide (H 2 O 2 ) produced by cell-surface NADPH Oxidase (Nox) enzymes is emerging as an important signaling molecule for growth, differentiation, and migration processes. However, how cells spatially regulate H 2 O 2 to achieve physiological redox signaling over nonspecific oxidative stress pathways is insufficiently understood. Here we report that the water channel Aquaporin-3 (AQP3) can facilitate the uptake of H 2 O 2 into mammalian cells and mediate downstream intracellular signaling. Molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
466
0
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 622 publications
(494 citation statements)
references
References 53 publications
4
466
0
7
Order By: Relevance
“…Relevant other sources of extracellular and intracellular H 2 O 2 include environmental exposure to ozone, UV light, and ionizing radiation (1,2). Among the most conserved defense mechanisms against the oxidizing effects of H 2 O 2 are detoxifying enzymes, such as catalase, as well as aquaporins that control the influx of H 2 O 2 into the cell (3)(4)(5)(6)(7). These mechanisms are highly efficient and adaptable, and provide an explanation for the great variation in susceptibility to H 2 O 2 among cell types despite the generally low intracellular concentrations across bacteria, plants, and mammals (3,8,9).…”
mentioning
confidence: 99%
“…Relevant other sources of extracellular and intracellular H 2 O 2 include environmental exposure to ozone, UV light, and ionizing radiation (1,2). Among the most conserved defense mechanisms against the oxidizing effects of H 2 O 2 are detoxifying enzymes, such as catalase, as well as aquaporins that control the influx of H 2 O 2 into the cell (3)(4)(5)(6)(7). These mechanisms are highly efficient and adaptable, and provide an explanation for the great variation in susceptibility to H 2 O 2 among cell types despite the generally low intracellular concentrations across bacteria, plants, and mammals (3,8,9).…”
mentioning
confidence: 99%
“…Altogether, these findings are reminiscent of results obtained in animal cells. A pioneering work using HyPer unraveled the role of AQP3 in H 2 O 2 transport and epidermal growth factor (EGF) signaling (31). This function was recently extended to NF-ÎșB signaling in keratinocytes (32) or in response to environmental stresses in colonic epithelia (33).…”
Section: Discussionmentioning
confidence: 99%
“…We 13 and others 17,[83][84][85] have shown that both AQP1 and AQP3 mediate uptake of H 2 O 2 in cells, postulating that transport of H 2 O 2 into mammalian systems by AQPs might interfere with intracellular signaling, amplifying cascades that depend on ROS, or increase the phosphorylation status of a cell (AKT/protein kinase B) and thus favor proliferation cascades.…”
Section: Glycerolmentioning
confidence: 99%
“…12,[38][39][40] In addition, several metabolically important small neutral solutes and ions have been identified as AQP substrates, namely hydrogen peroxide (H 2 O 2 ). 13,17,41,42 carbon dioxide, 43,44 nitric oxide, 45,46 ammonia, 47,48 metalloids such as arsenite and antimonite, 49-51 selenite, 52 boric acid, 53 and silicic acid. 51 AQP6 with low intrinsic water permeability may function primarily as an anion transporter.…”
Section: Aqp Permeability To Small Solutesmentioning
confidence: 99%
See 1 more Smart Citation